Improvement of Corn Plant Yield Through the Application of Biochar and Trichocompost from Rice Harvest Waste - Rini Suryani; Sutikarini Sutikarini; Agusalim Masulili; Agus Suyanto (STKIP Singkawang, 2023)
This research aimed to determine the optimal dosage of biochar and rice straw trichocompost for improving corn plant yield on Ultisol soil. The study was designed using a field experiment method with a Split Plot Design, consisting of two treatment factors. The first treatment factor was biochar with three levels: B0 = without biochar, B1 = 10 tons/ha, and B2 = 15 tons/ha. The second treatment factor was rice straw trichocompost with four levels: K0 = without trichocompost, K1 = 10 tons/ha, K2 = 15 tons/ha, and K3 = 20 tons/ha. The observed parameters for corn plant yield were cob length, cob diameter, dry weight of corn cobs, and dry weight of corn grains. The data collected from the observations were analyzed using an F-test at a significance level of 5%, followed by a Tukey test for further analysis. The results of the research indicated a significant effect of individual treatments of paddy straw biochar and rice straw trichocompost on corn plant yield, but there was no interaction between the treatments on corn yield in Ultisol soil. The optimal dosage of biochar for improving corn plant yield in Ultisol soil was found to be between 10 to 15 tons/ha. Meanwhile, the best dosage of rice straw trichocompost for enhancing corn plant yield in Ultisol soil was between 15 to 20 tons/ha.